Model Pelaksanaan Pengarusutamaan Gender Dalam Program Keindahan, Kebersihan dan Ketertiban (K3) di Kota Lhokseumawe - Nuribadah, Nuribadah; Iskandar, Hadi; Jafar, Sofyan; Sari, Elidar; Rahman, Arif; Sari, Purnama (Seminar Nasional Lahan Suboptimal, 2023)
Nuibadah, N., Iskandar, H., Jafar, S., Sari, E., Rahman, A., Sari, P. (2023). Implementation model for gender mainstreaming in the beauty, cleanliness and order (K3) program in Lhokseumawe City. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-11 Tahun 2023, Palembang  21 Oktober 2023. (pp. 65–77).  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The text discusses the implementation model of the K3 Program in Lhokseumawe City, which focuses on beauty, cleanliness, and order. The program aimed to ensure equal participation from both men and women in development. However, social norms and gender inequality often marginalize women, preventing them from accessing and governing the K3 programs. The research method used is qualitative, employing a sociological empirical/juridical approach. Primary and secondary data were collected through interviews with selected individuals who represent the relevance of the research. The results reveal a model for implementing gender mainstreaming in the K3 Program, which includes direct and indirect supervision, providing equal opportunities for men and women, and program monitoring and evaluation. Challenges in implementing gender mainstreaming in Lhokseumawe City include a lack of concern among individuals, erosion of ethics and morals, and the absence of a Standard Operating Procedure (SOP). Efforts made to address these challenges include creating a website on gender issues, involving women in all stages of the program, forming a women's community, and reviving abandoned clean-up activities. It is recommended that women be involved in the drafting of SOPs for the implementation of the K3 Program and Qanun orderliness.